2007
DOI: 10.12693/aphyspola.111.737
|View full text |Cite
|
Sign up to set email alerts
|

The Irreversibility Fields of (Tl0.5Pb0.5) (Sr0.85Ba0.15)2Ca2Cu3OzFilm on Polished Silver Substrate

Abstract: Superconducting (Tl0.5Pb0.5)(Sr0.85Ba0.15)2Ca2Cu3Oz film was prepared on a highly polished, untextured silver substrate. A superconducting transition temperature (T c,50% ) of 114.7 ± 0.3 K was obtained from the resistance versus temperature measurements for different applied ac currents. The density of the critical current measured by transport method was found to be 11.4×10 3 A/cm 2 at 77 K in the self field. This value is smaller than the value calculated from ac susceptibility data: 53 × 10 3 A/cm 2 at 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…On the other hand, higher than 2/3 values of m suggest the pinning force is weak and the vortex structure is like in HTS. These results are consistent with the temperature dependence of the critical currents and of the irreversibility elds [15,16]. The interesting features of the broadening of the resistive transition may be observed in the (Tl 0.5 Pb 0.5 )Sr 2 (Ca 1−x Gd x )Cu 2 O z superconductors (see Fig.…”
Section: Width Of the Resistive Transitionsupporting
confidence: 86%
“…On the other hand, higher than 2/3 values of m suggest the pinning force is weak and the vortex structure is like in HTS. These results are consistent with the temperature dependence of the critical currents and of the irreversibility elds [15,16]. The interesting features of the broadening of the resistive transition may be observed in the (Tl 0.5 Pb 0.5 )Sr 2 (Ca 1−x Gd x )Cu 2 O z superconductors (see Fig.…”
Section: Width Of the Resistive Transitionsupporting
confidence: 86%
“…After the discovery of some ceramic materials with a temperature of more than 90 K, which were referred to as high-temperature superconductors, superconductors entered a new stage. The ability to use liquid nitrogen for cooling [3] and liquid nitrogen at a temperature of (77 K), which can be obtained readily and at an affordable price [4,5], and the discovery of these materials have mad. When materials are cooled to a specific temperature, known as the critical temperature Tc, they become superconducting, allowing electric current to flow without resistance and with no magnetic flux at all.…”
Section: Introductionmentioning
confidence: 99%
“…Research is still going on to find superconducting materials with higher critical temperatures so that the applications are more readily available. Liquid nitrogen at a temperature (77 K), which can be obtained easily and at an appropriate cost [4,5], is another option. Tl-1223 was discovered to have two configurations in general: A pure compound is TlBa2Ca2Cu3O9 [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is now known that partial substitution of the Tl +2 layer in the Tl-O layer by cations which have higher oxidation states than Hg +2 , Ni +2 , Bi +4 , Pb +4 , and Cu +3 [7][8][9][10]. It improves stability and makes the synthesis of the single-phase material readily possible, and it has been found that the partial substitution of Sb2O3 for Tl2O3 helps stabilize the composition of the high Tc superconducting material, thus increasing the fraction size of this phase.…”
Section: Introductionmentioning
confidence: 99%